Vanished [large type] - Elliot, Kendra (Elliot, Kendra. Callahan & McLane., 2017)
"When an eleven-year-old is abducted on her way to school, the FBI immediately responds. Special Agent Ava McLane and local detective Mason Callahan work together to hold the family together and find themselves drawn to each other"--